British Malta, 1798-1835 - Zwilling, Andrew T., author.
1 online resource.
Keywords: "British Malta, 1798-1835 explores the incorporation and early administration of Malta as a British protectorate, and later as a Crown colony. Scholars and general readers drawn to the history of Malta, the British Mediterranean, and the expansion of the British Empire will find value in this narrative history"--